Credit derivatives and loan yields. Issue 1 (1st September 2021) - Azam, Nimita; Mamun, Abdullah; Tannous, George F.
Abstract: We compare the loan yields of credit derivative (CRD) active bank holding companies (BHCs) with the loan yields of CRD inactive peers over the pre‐crisis, crisis (2008–10), and post‐crisis periods. During the post‐crisis period, protection purchasers report lower yields than their peers, while sellers report yields like those reported by their peers. The relation between the yield and commercial and industrial (C&I) loans is positive and significant during the pre‐ and post‐crisis periods, and CRD activities do not affect this relation. CRD activities are changing the relations between the loan yield and consumer loans, real estate loans, and securitization.